Teologi Pernikahan Dalam Kitab Hosea - Paramita Rosdi Hutagalung; Rahul Sihombing; Rinaldi J K Lumban Toruan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The theology of Hosea's marriage to Gomer is used as a metaphor for the relationship between God and His people. Through theological analysis and historical context of the Book of Hosea, this research highlights the importance of maintaining purity, holiness, and love in Christian marriage to build a relationship that is pleasing to God. Quantitative research methods were used to collect data from reliable literature studies, with the aim of strengthening the concept of fidelity in the context of marriage and emphasizing the spiritual values contained in the marriage relationship. The story of the marriage of Hosea and Gomer in the Book of Hosea is considered a symbol of Israel's unfaithfulness to God, which teaches the importance of maintaining purity and holiness in Christian marriage, and emphasizes the role of love in building a husband and wife relationship that is pleasing to God. This research provides in-depth insight into marital relationships in theological and historical contexts, as well as underscoring spiritual values that can be applied in everyday life to glorify God through a loving and faithful marital relationship.